Submarine Groundwater Discharge in the Nice Airport Landslide Area - Christoph Witt; Achim Kopf (Journal of Marine Science and Engineering)
Natural radioactivity was measured and analyzed at the Nice Slope for over a month using radon daughters in order to trace groundwater movement from a coastal aquifer to a nearshore continental shelf. Such groundwater movement may have resulted in submarine groundwater discharge (SGD) and potentially sediment weakening and slope failure. The relationship among major hydrological parameters (precipitation, Var discharge, groundwater level, salinity and water origin) in the area is demonstrated in this study. Time series analyses also helped to detect tidal fluctuations in freshwater input, highlighting the crucial role SGD plays in the slope stability of the still failure-prone Nice Slope, parts of which collapsed in a tsunamigenic submarine landslide in 1979. Earlier deployments of the underwater mass spectrometer KATERINA showed that SGD is limited to the region of the 1979 landslide scar, suggesting that the spatially heterogenous lithologies do not support widespread groundwater charging. The calculated volumetric activities from groundwater tracing isotopes revealed peaks up to ca. 150 counts 214Bi, which is similar to those measured at other prominent SGD sites along the Mediterranean shoreline. Therefore, this rare long-term radioisotope dataset is a valuable contribution to the collaborative research at the Nice Slope and may not remain restricted to the unconfined landslide scar but may charge permeable sub-bottom areas nearby. Hence, it has to be taken into account for further slope stability studies.